Assessments of pollution status and human health risk of heavy metals in permafrost-affected soils and lichens: A case-study in Yamal Peninsula, Russia Arctic. Issue 8 (17th November 2019) - Ji, Xiaowen; Abakumov, Evgeny; Polyakov, Vyacheslav
Abstract: The active mining activities have occurred intensively in Yamal Peninsula, Russia Actic, which may cause hazardous effects on local workers and indigenous Inuts. Geoaccumulation Index ( I geo ), pollution Load Index (PLI), transfer factors (TFs), and hazard quotient (HQ) were utilized to the pollution level and human health risk of heavy metals in this region. Twenty samples of soil profile and five lichens were collected in this region. The highest concentrations of heavy metals were discovered in mining areas with a decreasing level of reference sites. Ni and Mn were the dominant metals in all sites. Cd, Ni, and Hg were beyond the regulatory threshold limit values. I geo shows that Hg was highly or extremely polluted in all sites; Ni was highly moderately to highly polluted only in mining areas. PLI shows soils in all areas were polluted more than one metal. TFs of lichens showed that Cr, Hg, Cu, and Ni were more accumulated in lichens, which may cause bioaccumulation in tundra terrestrial ecosystem. (HQ) presented no health risk for adults as regarding heavy metals, while Ni, Mg, and Hg may cause potential health risks for the local children via soil ingestion. GRAPHICAL ABSTRACT: